The longitudinal relationship between hearing loss and cognitive decline in tonal language-speaking older adults in China - Fu, Xinxing; Eikelboom, Robert H.; Liu, Bo; Wang, Shuo; Jayakody, Dona M. P. (Frontiers in Aging Neuroscience, 2023)
Previous longitudinal studies indicate that hearing loss and cognitive impairment are associated in non-tonal language-speaking older adults. This study aimed to investigate whether there is a longitudinal association between hearing loss and cognitive decline in older adults who speak a tonal language. Chinese-speaking older adults aged 60 years and above were recruited for baseline and 12-month follow-up measurements. All participants completed a pure tone audiometric hearing test, Hearing Impaired-Montreal Cognitive Assessment Test (HI-MoCA), and a Computerised Neuropsychological Test Battery (CANTAB). The De Jong Gierveld Loneliness Scale was used to measure loneliness, and the 21-item Depression Anxiety Stress Scale (DASS-21) was used to measure aspects of mental health. Associations between baseline hearing loss and various cognitive, mental and psychosocial measures were evaluated using logistic regression. 71 (29.6%) of the participants had normal hearing, 70 (29.2%) had mild hearing loss, and 99 (41.2%) had moderate or severe hearing loss at baseline, based on mean hearing thresholds in the better ear. After adjusting for demographic and other factors, baseline moderate/severe audiometric hearing loss was associated with an increased risk of cognitive impairment at follow-up (OR: 2.20, 95% CI: 1.06, 4.50). When PTA was modelled continuously, an average difference of 0.24 in HI-MoCA scores for every 10 dB increase in BE4FA existed, and an average difference of 0.07 in the change of HI-MoCA scores in a 12-month period. The results revealed a significant longitudinal relationship between age-related hearing loss and cognitive decline in this cohort of tonal language-speaking older adults. Steps should also be taken to incorporate hearing assessment and cognitive screening in clinical protocols for older adults 60 years and above in both hearing and memory clinics.